Interposition arthroplasty: an epochal event in a case of bilateral post burn contracture of elbow - Joshi, Gururaj; BM, Naveen; Gupta, Tej Pratap (International Journal of Research in Medical Sciences, 2016)
A 21 year old female, suffered accidental burns in April 2008 resulting in severe soft tissue contractures and bony ankylosis of both elbows. She was disabled with both nonfunctional upper extremities and reported to our center with deformity and dysfunction of both elbows for past 02 years. On evaluation her elbows were fixed in 40° flexion on right side and 30° flexion on left side. She was completely dependent on her mother for her daily activities like feeding and hygiene care, though she had acceptable wrist and hand function. She was managed with interposition arthroplasty with ipsilateral autogenous tensor fascia lata graft on both elbows. At 5 year follow-up, she has pain free elbows with functional range of motion and no neurovascular deficits. She is able to use both upper extremities for all activities of daily living. Most importantly she is independent and has taken up a job for her livelihood.